Pengaruh konsentrasi Plant Growth Promoting Rhizobacteria terhadap intensitas kerusakan akibat penyakit layu fusarium (Fusarium oxysporum f. sp lycopersici) dan produksi tanaman tomat (Lycopersicum esculentum Mill.) - Wahyudi; Ruimassa, Reymas M. R.; Martanto, Eko Agus; Mogea, Rina A.; Purnomo, D. Wasgito (Program Pascasarjana Universitas Papua, 2024)
ABSTRACT: The research aims to determine the effect of PGPR application on the incidence of fusarium wilt disease and tomato plant production. The research was carried out using a Randomized Group Design (RAK) with one treatment factor, namely the PGPR dose. Treatment was made in five levels, namely D0 (control/no PGPR), D1 (5 cc PGPR/liter air), D2 (10 cc PGPR/liter air), D3 (15 cc/liter air) and D4 (20 cc PGPR/liter air air). The results of in vitro PGPR testing provided an inhibitory response to Fusarium growth with an average of 47.32% on PDA media and 63.12% on NA media. The PGPR dose treatment tested did not have a significant effect on plant height, number of leaves, production characteristics and disease intensity, except for the average number of branches per tree, root length and root weight. Giving a dose of 20 cc/liter is the best dose to increase root character and number of branches.